Cadê o Kauê? Co-design and acceptability testing of a chat-story aimed at enhancing youth participation in the promotion of mental health in Brazil - Pavarini, G; Murta, SG; Mendes, JAA; Siston, FR; Souza, RRA; Cunha, RO; Ferreira, JA; Santos, VHL; Seabra, BTR; Talk2U; Singh, I (Wiley, 2024)
Background: Adolescent mental health is vital for public health, yet many interventions fail to recognise adolescents as proactive community contributors. This paper discusses the co-design and acceptability testing of a chat-story intervention to enhance Brazilian adolescents' participation in the promotion of mental health in their peer communities. We specifically highlight the iterative process of co-creating this intervention with community stakeholders. Methods: The co-design was led by researchers, a youth collaborative group, and health-tech experts. Part 1 included quantitative (n = 1,768) and qualitative (n = 46) studies with Brazilian adolescents aged 15–18 for priority-setting. Part 2 involved co-creation and technical production, with input from youth advisors (n = 24), school staff (n = 11), and policy experts (n = 3). In Part 3, the chat-story was user tested (n = 32). Parts 4 and 5 assessed acceptability through a qualitative study in schools (n = 138) and initial efficacy during an online campaign (n = 795). Results: Participants aspired to support their peers' mental health in schools, both one-to-one and collectively, but felt unprepared. This informed the chat-story's goal of enhancing peer support and collective action skills. Themes identified during Part 1, such as prejudice and academic pressure, were woven into the narrative to raise awareness of the social determinants of mental health, drawing from real-life stories. In the final story, players search for their missing best friend at school, uncovering his anxiety struggles and practicing skills such as empathic listening and partnership building. A manual for teachers was collaboratively designed for use within school settings, supplementing direct-to-user online applications. Acceptability testing showed participants found the tool authentic and user-friendly. Online users perceived the tool as preparing and motivating them to offer peer support and engage in collective action. Conclusions: The immersive co-creation model, enriched by input from key stakeholders, yielded a relevant and well-received intervention for Brazilian adolescents. Co-designed creative tools like chat-stories hold promise as digital mental health tools, fostering awareness, critical reflection, and inspiring adolescents to drive positive social change.